Premature repayment of fixed interest mortgage loans without compensation, a case of misguided consumer protection in the EU - Hans-Bernd Schäfer; Alexander J. Wulf (European Journal of Law and Economics, 2022)
Consumer protection shifts risks from consumers to businesses. This raises marginal costs and equilibrium prices. It is justified when markets are not strong enough to allocate contractual risks or accident risks efficiently, especially in cases of severe asymmetric information between suppliers and consumers. Consumer protection can then increase the consumer's expected welfare from a contract. We test these considerations in a theoretical and empirical study on consumers' right to early repayment of mortgage loans without damage compensation to the creditor in the European Union. We show in a formal model that such a right can lead to an impairment of consumer welfare, compared with the traditional rule of expectation damages for breach of contract. This applies if the consumer is risk averse and repays a loan with a high interest rate in a low interest period to take up a new loan for the same project at lower interests. From a theoretical point of view, this right has no solid economic underpinning, if it is not restricted to cases of personal hardship of the consumer and serves an insurance purpose. We present empirical evidence supporting this argument. In a panel study on monthly mortgage interest rates of 23 EU Member States between 2005 and 2017 we show how interest rate spreads change with the level of consumer protection.
Keywords: K12; K22; K25; G12; G18; 340; Consumer contract law; Consumer protection; Mortgage loans; Financial services; Regulation; EU law